Elementary students’ shared understanding of angle during an educational robotics task - Simpson, Amber; Shokeen, Ekta; Katirci, Nihal; Williams-Pierce, Caro (Frontiers in Education, 2024)
Prior research has documented students' struggles in conceiving of angle and angle measurement, which may stem from textbook and curriculum representations of angles as static. In this study, we examined grade 3-5 students' mathematical thinking of angle during an educational robotics task implemented within a making space learning environment in a school setting (i.e., hybrid making space). Our analysis included 19 video recordings of six groups of students. Results from this study demonstrate how students negotiated a shared understanding of angle through multiple epistemic tools (e.g., gestures, bodily actions, language) that were situated and contextualized within the task. This included developing a shared language, conceptualizing angle as a dynamic entity, and perceiving angle through directionality and degree measures. We contend that learning experiences within a hybrid making space provide young students with opportunities to engage in mathematics as a social phenomenon and human activity.